2016
DOI: 10.1371/journal.pone.0166012
|View full text |Cite
|
Sign up to set email alerts
|

Role of Patient and Practice Characteristics in Variance of Treatment Quality in Type 2 Diabetes between General Practices

Abstract: BackgroundAccounting for justifiable variance is important for fair comparisons of treatment quality. The variance between general practices in treatment quality of type 2 diabetes (T2DM) patients may be attributed to the underlying patient population and practice characteristics. The objective of this study is to describe the between practice differences in treatment, and identify patient and practice level characteristics that may explain these differences.MethodsThe data of 24,607 T2DM patients from 183 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…Nevertheless, it has been reported that patient case‐mix and deprivation do not explain the majority of variation in treatment target achievement . Previous studies, which found only modest associations between variations in GP practice and differences in patient and/or GP practice characteristics, suggest that the variation may be related, rather, to differences in local organization and health systems . For example, a meta‐analysis of strategies for quality improvement in diabetes care revealed that strategies targeting the organization of healthcare, such as changes in organization of primary healthcare team and facilitated relay of clinical information to clinicians, were more successful than strategies directed at healthcare professionals or patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it has been reported that patient case‐mix and deprivation do not explain the majority of variation in treatment target achievement . Previous studies, which found only modest associations between variations in GP practice and differences in patient and/or GP practice characteristics, suggest that the variation may be related, rather, to differences in local organization and health systems . For example, a meta‐analysis of strategies for quality improvement in diabetes care revealed that strategies targeting the organization of healthcare, such as changes in organization of primary healthcare team and facilitated relay of clinical information to clinicians, were more successful than strategies directed at healthcare professionals or patients .…”
Section: Discussionmentioning
confidence: 99%
“…1,20 Previous studies, which found only modest associations between variations in GP practice and differences in patient and/or GP practice characteristics, suggest that the variation may be related, rather, to differences in local organization and health systems. [21][22][23] For example, a meta-analysis of strategies for quality improvement in diabetes care revealed that strategies targeting the organization of healthcare, such as changes in organization of primary healthcare team and facilitated relay of clinical information to clinicians, were more successful than strategies directed at healthcare professionals or patients. 13 A qualitative systematic review identified the following barriers to achievement of effective management of T2D in primary care: firstly, uncertainties in professional roles and responsibilities as the result of changes in the structural boundaries between primary and secondary care; and secondly, lack of training in approaches to facilitate behavioural changes in patients.…”
Section: Impact Of Achieving Treatment Targets On Health Outcomes Amentioning
confidence: 99%
“…Regarding the fact that differences in glucose-lowering treatment are partly explained by complications and intolerances reflecting the polypharmacy associated with complex comorbidities, insulin therapy could be favored in T2D patients with complex comorbid status. [ 8 ] In addition, a recent study found that the combination of insulin with oral glucose-lowering drugs afforded several potential advantages without compromising glycemic efficacy. [ 35 ] In a recent retrospective analysis of the UK General Practice Database (including 91,511 type 2 diabetes patients with a follow-up time of 7.1 years), TZD (pioglitazone) combined with MET appeared to provide superior clinical outcomes; all-cause mortality, major adverse cardiovascular events, stroke; compared with the most commonly used regimen, MET+SU, or SU monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 7 ] However, standard recommendations are increasingly criticized as contributing to excessive treatment that is sometimes futile. Variations in guideline-recommended treatments have been noted in practice, [ 8 ] and several studies have emphasized that current standard diabetes treatment recommendations do not appropriately consider individuals with complex comorbidities. [ 9 , 10 ] The identification of common comorbidity patterns and the exploration of current treatment status in terms of such comorbidities may improve the approach of management of T2D and associated comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Practice characteristics including rurality and size influence access to health care, [1][2][3] the type and frequency of screening and testing, [4][5][6] chronic disease management 7 and hospital admission. [8][9][10][11] The size and location of practices may affect the quality and safety of health care in other ways.…”
Section: Introductionmentioning
confidence: 99%